Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Guru - Atiyyah, Jazilatul; Hamdiah, Hamdiah; Febriyanti, Ella; Serlly, Serlly; Salfika, Nofi Fitri; Ernanto , M. Rangga; Sales, Rocky Nathaniel R (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2024)
This study aims to see and assess what are the direct and indirect influences that affect teacher performance which are influenced by the principal's leadership variable, work environment and work motivation in high school in Muaro Jambi. In research using a quantitative approach and survey techniques were chosen as the data collection technique in this study that was used was distributing questionnaires to the respondents. The subjects in this study were teachers at SMA Muaro Jambi with a total sample of 250 teacher in SMA Muaro Jambi using gpower to determine the amount of sampling. The data collection technique uses a questionnaire which is distributed and collected via Googleform. Quantitative data analysis using the PLS-SEM method. The results of this study indicate that (1) the principal's leadership influences teacher performance, (2) the work environment influences teacher performance, (3) work motivation influences teacher performance, (4) principal's leadership influences work motivation, (5) work environment affects work motivation, (6) principal leadership influences teacher performance mediated by work motivation and (7) work environment influences teacher performance mediated by work motivation. So, principal leadership, work environment and work motivation influences teacher performance SMA in Muaro Jambi. Keywords: Teacher Performance, Principal Leadership, Work Environment, Work Motivation.